Instant Noodle Production Information System Using The Method Supply Chain Management To Overcome Targets Not Achieved - Muhammad Helmi Farhan; Suendri Suendri (Information Technology and Science (ITScience), 2023)
Improvement This research aims to analyze and implement an instant noodle production information system using the Supply Chain Management (SCM) method to overcome the inability to achieve predetermined production targets. In this study, an analysis was carried out on the entire supply chain in the production of instant noodles, which includes raw material suppliers, production processes, distribution and sales. The research method used is a qualitative method. The subjects of this study were instant noodle company employees. The results showed that the application of a production information system using the SCM method could help companies increase the efficiency of instant noodle production. With an integrated information system, companies can gain better visibility on consumer demand, raw material inventory, and production status. This allows companies to carry out more accurate production planning, accelerate production cycle times, and optimize resource use